Peutz-Jeghers disease: most, but not all, families are compatible with linkage to 19p13.3. Issue 1 (January 1998) - Olschwang, S; Markie, D; Seal, S; Neale, K; Phillips, R; Cottrell, S; Ellis, I; Hodgson, S; Zauber, P; Spigelman, A; Iwama, T; Loff, S; et al.
Abstract : A locus for Peutz-Jeghers syndrome (PJS) was recently mapped to chromosome 19p13.3. Each of 12 families studied was compatible with linkage to the marker D19S886. We have analysed 20 further families and found that the majority of these are consistent with a PJS gene on 19p13.3. Three families were, however, unlinked to 19p13.3 and none of the available PJS polyps from these families showed allele loss at D19S886. There were no obvious clinicopathological or ethnic differences between the 19p13.3 linked and unlinked families. There appears, therefore, to be a major PJS locus on chromosome 19p13.3 and the possibility exists of a minor locus (or loci) elsewhere.